Las nuevas tecnologías de la información y la educación científica temprana. Una revisión - Ordóñez Morales , Óscar (2010)
This article shows an overview of recent psychological literature about relation between children’ s scientific understanding and new technologies of information used in educa- tional contexts. The aim is to ar gue that both, scientific education and early children’ s scientific rationality may be support by environmental learning based on information technologies and learning networks. The literature review includes studies that link cog- nitive development with scientific education; studies that demonstrates how technolo- gies of information af fect to early scientific understanding; and studies about the role played by virtual technologies in descriptive research about the cognitive processes in- volved in scientific thinking. Along the review , an assessment is made focused on some future trends in the area . W e conclude that to implement learning networks in educatio- nal contexts improves better achievements in early scientific education